Using the temporal self-regulation theory to examine the influence of environmental cues on maintaining a healthy lifestyle - Booker, L.; Mullan, Barbara (John Wiley & Sons Ltd., 2013)
Objectives: The aim of the current study is to explore the predictive utility of the temporal self-regulation theory (TST) for maintaining a healthy lifestyle (Hall & Fong, 2007, Health Psychology Review, 1, 6). According to TST, the influence of intention, self-regulation, and behavioural pre potency differs depending on the environmental context in which the behaviour is performed. This study examined the influence of perceptions about the supportiveness of the environmental context on TST-related factors.Design: Temporal self-regulation theory was tested using a prospective design with a 1-week follow-up.Methods: One hundred and fifty-two undergraduates were administered three executive functioning tasks and an online questionnaire regarding their intentions to maintain a healthy lifestyle, environmental responsiveness, and previous behaviour. One week later, they completed a follow-up questionnaire.Results: Participants who were supported by the environment were significantly more likely to maintain a healthy lifestyle than those distracted by the environment. Behavioural pre potency was significantly predictive of behaviour performance for ‘supported’ participants. Behavioural pre potency, planning, and response inhibition were significantly predictive of ‘unsupported’ participants’ behaviour.Conclusions: These findings provided preliminary support for the use of TST for the prediction of healthy lifestyle behaviour. Importantly, this study provided support for the contention that the influence of TST-related factors would vary according to the perceived supportiveness of the environment. These findings suggest that environmental responsiveness may be an important determinant to close the intention–behaviour gap for maintaining a healthy lifestyle.